A cultura patriarcal e a representatividade feminina: Um estudo sobre a inserção das mulheres em cursos de agrárias de uma universidade do Sul de Minas - Paula, Flávia Caroline Alves de (2020)
Discussing sustainable development, only from the environmental and economic perspective of natural resources, failing to consider important social aspects, namely: relations of social equity and equal opportunities, minimum guarantees of access to the needs of all human beings, it is done superficial with the proposal of sustainability, democracy and participation. Starting from the relevance of a development that mainly comprises socio-cultural issues, with this research, I sought as a guiding question the following question: In what ways does the naturalization of socio-cultural processes of discrimination against women occur in UFLA's agricultural science courses? Does the naturalization of professional stereotypes interfere with academic choices? Are there any relations between this naturalization and the patriarchal system? With the study, I had as main purpose to investigate how the processes of naturalization of spaces of male power take place and how they interfere in the insertion and academic performance of women in the agrarian courses at UFLA. With a specific character, I tried to: examine the history of entry of women who make up the agrarian area of this university, who were inserted in the degrees of Agricultural Engineering, Food Engineering and Zootechnics, between the years 2013 to 2017; evidence in which of these courses, such women are in greater / lesser quantitative representation; verify what guided them (the motivations) in choosing these courses; identify the challenges faced by them in the scope of teaching, research, extension; investigate and present the strategies mobilized by these university students in favor of academic performance and subsequent access to the job market. The methodological path that I used is structured through a mixed descriptive research, together with the data provided by UFLA's Pro-Rectory of Graduation (PRG), between the years 2013 and 2017, in order to locate in which courses of the large area of agrarian sciences, women are in a greater and lesser proportion, also considering their tradition. Subsequently, I carried out a case study with semi-structured interviews with the students enrolled in the three selected courses and who are inserted in representative groups such as study, research and extension centers; Tutorial Education Program (PET‟s); junior companies, and the respective coordinators of these groups, in order to understand the proposed objectives. For this, I tried to delimit a sample for convenience, covering the courses selected in the pre-established time period. Keywords: Gender. Male domination. Agrarian Sciences. Naturalization